2022
DOI: 10.3389/fmicb.2021.822229
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genomics Sheds Light on Evolutionary Forces Shaping the Acidithiobacillia Class Acidophilic Lifestyle

Abstract: Extreme acidophiles thrive in environments rich in protons (pH values <3) and often high levels of dissolved heavy metals. They are distributed across the three domains of the Tree of Life including members of the Proteobacteria. The Acidithiobacillia class is formed by the neutrophilic genus Thermithiobacillus along with the extremely acidophilic genera Fervidacidithiobacillus, Igneacidithiobacillus, Ambacidithiobacillus, and Acidithiobacillus. Phylogenomic reconstruction revealed a division in the Aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 181 publications
0
10
0
Order By: Relevance
“…In addition, ‘ Igneacidithiobacillus ’ spp. genomes/MAGs were found to encode genes for the biosynthesis of hopanoids ( hpnABFGHIJKLMN ) ( Supplementary Table S7 ), as all acidophilic members of the Acidithiobacillia class do ( González-Rosales et al, 2022 ), which have been shown to decrease membrane fluidity in bacteria under pH stress ( Sáenz et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, ‘ Igneacidithiobacillus ’ spp. genomes/MAGs were found to encode genes for the biosynthesis of hopanoids ( hpnABFGHIJKLMN ) ( Supplementary Table S7 ), as all acidophilic members of the Acidithiobacillia class do ( González-Rosales et al, 2022 ), which have been shown to decrease membrane fluidity in bacteria under pH stress ( Sáenz et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Present study deals with characterization of the kdpFABC complex in the halotolerant bacterium A. xylosoxydans. Multiple studies identified the presence of kdp ATPaseencoding genes in many halotolerant bacteria, but no one has characterized this complex protein (Gumulya et al, 2018;González-Rosales et al, 2022;Najjari, 2023). Therefore, this is the first-ever study reporting the characterization of proteins constituting the kdp ATPase complex.…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ], and González-Rosales et al . [ 35 ]. However, scant attention has been paid to the adaptations of extracellular protein structures, such as T4P, which remain vulnerable to low pH due to their exposure outside the cell.…”
Section: Introductionmentioning
confidence: 99%